2011
DOI: 10.2169/internalmedicine.50.5844
|View full text |Cite
|
Sign up to set email alerts
|

Association of Short Sleep Duration with Obesity, Diabetes, Fatty Liver and Behavioral Factors in Japanese Men

Abstract: Objective Sleep is one of the major means to maintain health. The association of short sleep duration with obesity, diabetes, fatty liver and behavioral factors requires further exploration. Methods A total of 8157 Japanese men who underwent health evaluations were divided into 3 groups by sleep duration <5 hours, 5~<7 hours and !7 hours. Poor sleep was self-reported, being defined as difficulty of getting to sleep or awakening easily. The age-adjusted and age and poor sleep-adjusted odds ratios of the 3 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 22 publications
3
59
2
Order By: Relevance
“…Members of younger and bigger households are also more likely to choose convenience food, while older households are more likely to maintain traditional meals 66 . Immigrants report that acculturation is often associated with an increase in stress 69,70,71 and stress and stress-related disorders may play an important role in the development of obesity 67,68 .…”
Section: Sub-saharan Africansmentioning
confidence: 99%
“…Members of younger and bigger households are also more likely to choose convenience food, while older households are more likely to maintain traditional meals 66 . Immigrants report that acculturation is often associated with an increase in stress 69,70,71 and stress and stress-related disorders may play an important role in the development of obesity 67,68 .…”
Section: Sub-saharan Africansmentioning
confidence: 99%
“…Since those reviews were published, additional support has been put forth from various population studies. [4][5][6][7][8][9] Although the literature is somewhat consistent, some studies do not show an association in specifi c population subgroups, such as the elderly.6,10 Nevertheless, it is generally agreed that there is a link between short sleep duration and obesity. However, whether this relationship is causal is debatable.…”
mentioning
confidence: 99%
“…3 Short sleep duration may be an important but unrecognized factor promoting obesity. 4 Population-based studies have reported a dose-response relationship between short sleep duration and high BMI, [5][6][7][8][9][10][11][12] and there may be an association with weight gain. 6,7,13,14 Voluntary sleep restriction is common: 28% of the adult population in the United States reports getting Յ 6 h of sleep per night.…”
mentioning
confidence: 99%